أثر جائحة كورونا على المدد التعاقدية والمدد القانونية في قانون المرافعات المدنية - الدراجى، علي عبدالحسين منصور (كلية الإمارات للعلوم التربوية, 2020)
The Corona pandemic was a huge surprise to the world, and no one had calculated it and put it in its power to repel it or reduce its risks, either in the health field or in other areas. In the field of law, that pandemic revealed to us the lack of national legislation that addresses the conditions imposed by various legal systems, this deficiency did not stop at national law, but even at the level of international law, international treaties and agreements, and others, at the level of the legislative system in Iraq, it is clear that there is a severe lack of legislation and rules that regulate legal relations and in almost all areas of law, the current circumstances revealed the inability of the legislation on how to deal with the consequences of exceeding legal periods under the new circumstance and the attendant curfew and its effects on the rules of pleadings in the courts or the effect of that on the periods stipulated in other laws, such as civil law, trade law and those stipulated in the transport law or the enforcement law.
كانت جائحة كورونا مفاجأة كبيرة بالنسبة للعالم، ولم يكن أحد قد تحسب لها ووضع لها ما يمكن لصدها أو التقليل من مخاطرها، سواء في المجال الصحي أو في غيره من المجالات الأخرى. وفي مجال القانون كشفت لنا تلك الجائحة النقص في التشريعات الوطنية التي تعالج الأوضاع التي فرضتها النظم القانونية المختلفة، ولم يقف ذلك النقص عند القانون الوطني بل حتى على مستوى القانون الدولي والمعاهدات والاتفاقيات الدولية وغيرها، وعلى مستوى المنظومة التشريعية في العراق يتضح إن هناك نقص شديد في التشريع والقواعد التي تنظم العلاقات القانونية وفي كل مجالات القانون تقريبا، وقد كشفت الظروف الحالية عجز التشريع عن كيفية معالجة الآثار التي تترتب عن تجاوز المدد القانونية في ظل الظرف المستجد وما صاحبه من حظر التجوال وأثاره على قواعد المرافعات في المحاكم، أو تأثير ذلك في المدد المنصوص عليها في القوانين الأخرى، كالقانون المدني وقانون التجارة وتلك المنصوص عليها في قانون النقل أو قانون التنفيذ.
Keywords: فيروس كورونا "كوفيد-19" -- المرافعات المدنية -- التوازن الاقتصادي -- القوانين العراقية